2009
DOI: 10.1186/1471-2415-9-1
|View full text |Cite
|
Sign up to set email alerts
|

CD133+adult human retinal cells remain undifferentiated in Leukaemia Inhibitory Factor (LIF)

Abstract: Background: CD133 is a cell surface marker of haematopoietic stem and progenitor cells. Leukaemia inhibitory factor (LIF), sustains proliferation and not differentiation of embryonic stem cells. We used CD133 to purify adult human retinal cells and aimed to determine what effect LIF had on these cultures and whether they still had the ability to generate neurospheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…& CD 133 (Prominin-1) (monoclonal mouse IG1, CD133/1, (AC 133, pure, Miltenyi, Biotec, 130-090-422, dilution 1/10) is a pentaspan protein membrane stem cell marker, specific to primitive human, mammalian, and mice hematopoietic and neural progenitor (PG) cells [23,24]. CD133+ cells are considered a quiescent PG cell population in the adult brain [25] and in the adult postmortem retina [26]. We have reported that CD133 is expressed at the external limiting membrane (ELM) level in the human fetal retina and in the adult human retina (Ducournau Y, Boscher C, Ducournau D, Guillaubey C, Mosnier JF.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…& CD 133 (Prominin-1) (monoclonal mouse IG1, CD133/1, (AC 133, pure, Miltenyi, Biotec, 130-090-422, dilution 1/10) is a pentaspan protein membrane stem cell marker, specific to primitive human, mammalian, and mice hematopoietic and neural progenitor (PG) cells [23,24]. CD133+ cells are considered a quiescent PG cell population in the adult brain [25] and in the adult postmortem retina [26]. We have reported that CD133 is expressed at the external limiting membrane (ELM) level in the human fetal retina and in the adult human retina (Ducournau Y, Boscher C, Ducournau D, Guillaubey C, Mosnier JF.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that some of these cells can be dormant or slow-cycling, and suggested that CD133 might be down-regulated during G0/G1 [32].Therefore, as we did observe CE rhodopsin expression, we cannot rule out the possibility of missing a period of transitory CD133 expression. Also, recent findings on the commitment of CD133+ retinal cells towards differentiation show that the process might be promoted by the cytokine leukaemia inhibitory factor (LIF), which is endogenously secreted in cases of neural tissue injury or damage [26]. The framework of the disease RD with PVR might be assimilated to damage, and might have promoted the differentiation of CE CD133+ cells into PR and negatived CD133 staining.…”
Section: Cd133mentioning
confidence: 96%
See 2 more Smart Citations
“…The continuous development of flow cytometry techniques to assess cell surface antigens has provided biomarkers that can be used to obtain highly purified tissue-specific RPCs. To date, several cell markers have proven to be suitable for the specific identification, isolation and enrichment of RPCs (Carter et al, 2009;Koso et al, 2009); these markers are invaluable for RPC research.…”
Section: Introductionmentioning
confidence: 99%